Ultrastructure of phagocytes from mammary glands of non-pregnant heifers - Sládek, Z; Rysánek, D (Anatomia, histologia, embryologia, 1999)
Results of ultramicroscopic investigations of phagocytes isolated from non-secreting and aberrantly secreting juvenile mammary glands of non-pregnant heifers are presented. The two types of phagocytes observed in cell suspensions obtained by lavage of mammary gland cavities were polymorphonuclear leukocytes and macrophages. Polymorphonuclear leukocytes were spherical or irregular in shape and contained segmented nuclei. Azurophilic and specific electron-dense granules, mitochondria, glycogen particles, phagosomes and phagolysosomes in cytoplasma and characteristic pseudopodia on the cell surface were observed. In addition to these normal polymorphonuclear leukocytes, degenerating cells, characterized by spherical nuclei, total absence of pseudopodia, merged nuclear segments and altered granules, other cellular organelles and plasmalemma were present. Two types of macrophages, i.e. vacuolized and non-vacuolized, could be distinguished. Typical of the non-vacuolized type was a kidney-shaped nucleus, a rich Golgi complex and a large amount of lysosomes in the cytoplasm. The vacuolized macrophages contained a large amount of electron-dense vacuoles in the cytoplasm. Unlike non-secreting glands, the cell suspensions collected from aberrantly secreting juvenile mammary glands contained only vacuolized macrophages. The vacuolization results from phagocytosis of corpuscular particles of aberrant milk plasma.
Keywords: mléčné žlázy zvířat; fagocyty; Female; makrofágy; Phagocytes; Animals; Macrophages; Cattle; ženské pohlaví; neutrofily; Vacuoles; vakuoly; Mammary Glands, Animal; zvířata; Neutrophils; skot